2014
DOI: 10.1364/ol.40.000017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ambient air on femtosecond laser ablation of highly oriented pyrolytic graphite

Abstract: Highly oriented pyrolytic graphite is ablated by femtosecond laser in air and vacuum, respectively. The morphologies and material components of the ablated target surface are examined by scanning electron microscopy and micro-Raman spectroscopy. For laser fluence no less than 0.5  J/cm(2), the laser-induced periodic surface grooves formed in air are found to be much less clearer than those formed in vacuum; beneath the amorphous carbon debris, the surface ablated in air is composed of nanocrystalline graphite,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 19 publications
3
7
0
Order By: Relevance
“…3b), which exhibit a relatively weak surface modulation with 10 a spatial period Λ = (872  62 nm). Analogue to HSFL and in good agreement to literature [29,33], the orientation of LSFL is also perpendicular to the linear beam polarization. For F < 1.6 J/cm 2 (not shown here), the possible transition between HSFL and LSFL was not observed because of the insufficient number of laser pulses.…”
Section: Formation Of Hsflsupporting
confidence: 89%
See 1 more Smart Citation
“…3b), which exhibit a relatively weak surface modulation with 10 a spatial period Λ = (872  62 nm). Analogue to HSFL and in good agreement to literature [29,33], the orientation of LSFL is also perpendicular to the linear beam polarization. For F < 1.6 J/cm 2 (not shown here), the possible transition between HSFL and LSFL was not observed because of the insufficient number of laser pulses.…”
Section: Formation Of Hsflsupporting
confidence: 89%
“…While the LIPSS formation on graphite was studied by several groups in dependence on different influencing parameters (beam polarization, laser peak fluence) on the flat surface of bulk materials [28][29][30][31][32], the formation of LIPSS on the surface of carbon fibers is less investigated [11,33]. By performing single-spot experiments on strongly curved fiber surfaces, Sajzew et al [33] demonstrated the formation of LSFL and HSFL within the Gaussian intensity 4 distribution of the focal spot (diameter 50 µm) upon the irradiation of N = 50 linearly polarized fs-laser pulses with a peak fluence F = 4 J/cm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Femtosecond laser patterning of CVD-grown graphene electrodes on silicon substrates and their application as source and drain electrodes in MOTFTs were studied. The quality of the patterned electrodes was improved by laserablation in vacuum due to debris reduction compared to laser processing in air which is consistent with previous reports on laser processing in vacuum [28][29][30]. Raman spectroscopy analysis showed that the I(2D)/I(G) ratios for samples processed in air and in vacuum (≈ 2) are comparable, which suggests that having air or vacuum as environment during patterning does not considerably influence the graphene layer.…”
Section: Resultssupporting
confidence: 88%
“…The problem however is that during laser patterning graphene forms folds [27] and debris causing disturbance resulting in unwanted defects and negative impact on its application as transistor electrodes. Femtosecond laser ablation of graphene in vacuum, compared to air, should result in cleaner and more controlled patterning of the layer because rather less material is redeposited on the substrate [28][29][30]. Moreover, atmospheric oxygen can oxidize the remaining graphene upon laser ablation and reduce performance of graphenebased electronics.…”
Section: Introductionmentioning
confidence: 99%
“…2(a). Different from that of the HOPG, the D band at about 1350 cm −1 appears in the Raman spectrum of the laser-exfoliated graphene, moreover, the D-band and G-band are broadened, which indicate that the exfoliated graphene was in a few-layers form [32].…”
Section: Preparation and Characterization Of Graphenementioning
confidence: 91%